(untitled) (Applied Biological Research, 2016)
A field experiment was conducted during rabi 2012-13 at Research-cum Instructional Farm, IGKV, Raipur, Chhattisgarh (India) to study the effects of seaweed saps on growth, yield, nutrient uptake and economic of potato in Inceptisol soil. Foliar spray of the extracts of two seaweeds (Kappaphycus and Gracilaria) was done on potato crop separately twice at different concentrations (0, 2.5, 5.0, 6. 25, 7.5 and 10.0% v/v). Foliar application of seaweed extract significantly enhanced growth, yield, nutrient uptake and benefit: cost ratio (B:C) in potato crop. The highest tuber yield was observed with the applications of 10% Gracilaria sap + recommended dose of fertilizer (RDF), followed by 10% Kappaphycus sap + RDF treatment showing 11.31 and 9.37% tuber yield increase, respectively, over control (water spray + RDF). The highest uptake of N, P and K by tuber and haulm was observed in 10% Gracilaria sap + RDF treatment. The highest net return ha-1 (Rs. 1,14,871) and B:C ratio (1.21) were observed with the application of 10%Gracilaria sap + RDF.